Penerapan Sistem Blok dalam Mendorong Kemandirian Belajar Bahasa Arab Siswa di MTs NU Pakis (MATSNUEPA) - fitri Amelia; Mukhlis, Sholehuddin; Alfarezy, Alfy; Daroini, Slamet (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STAI DR. KHEZ. Muttaqien Purwakarta, 2024)
The Merdeka Curriculum has a principle of freedom in learning that guides students to become independent learners. MTs NU Pakis (MATSNUEPA) uses a block system as its learning system. With this block system, the duration of student learning becomes longer in each lesson. Thus, students are encouraged to be independent learners. Based on this, the aim of this research is to explore how the application of the block system can encourage students' independent learning in Arabic language learning, as well as the forms of independent learning carried out by students in the Arabic language subject. This research uses a qualitative method with a case study approach. Data collection uses three instruments in the form of interviews, observations, and documentation. Data analysis is carried out using Miles and Huberman's theory through three stages: reducing data, presenting data, and drawing conclusions. The results of this study indicate that the implementation of the block system based on the Merdeka curriculum is divided into four blocks in each academic year. The forms of students' independent learning are implemented through project-based learning methods, the use of learning media, and tourism activities at the end of each semester.